Photophysical and photochemical studies on non-peripherally and peripherally Ga(III) chloro phthalocyanines in different solvents - Guney, Gunseli; Gorduk, Semih (ELSEVIER SCIENCE SA, 2023)
Phthalocyanine compounds display strong absorbance during their interaction with light thanks to the delocalized & pi; bonds. In recent years, the studies have been carried out to use phthalocyanine compounds, which are sensitive to light, as photosensitizers in the singlet oxygen production.In present work, two different phthalonitrile derivatives were separately obtained as a result of the reaction of 3-nitrophthalonitrile and 4-nitrophthalonitrile compounds with 2-hydroxymethyl-1,4-benzodioxane. As a result of the reaction of these phthalonitrile derivatives with gallium(III) metal ion, non-peripherally and peripherally 2-hydroxymethyl-1,4-benzodioxane substituted gallium(III) phthalocyanines (3-GaPc and 4-GaPc) were separately obtained. The synthesis of the compounds was performed by conventional methods and the characterization processes were carried out using ultraviolet and visible light (UV-vis) absorption spectroscopy, infrared (IR) spectroscopy, proton nuclear magnetic resonance (1H NMR ) spectroscopy and matrix assisted laser desorption/ionization mass spectroscopy (MALDI TOF MS) methods. Photophysical, photochemical and aggregation properties of two gallium(III) phthalocyanine compounds were investigated in different solvents such as dimethylformamide (DMF), dimethyl sulfoxide (DMSO), tetrahydrofuran (THF) and toluene solvents for their usability in singlet oxygen generation. Solvents have an effect on the results. The result show that these compound display good solubility and suitable singlet oxygen generation properties in the mentioned solvents.
Keywords: Phthalocyanine; Gallium(III); Aggregation; Photodynamic therapy; Singlet oxygen; SUBSTITUTED GALLIUM; QUANTUM YIELDS; METALLOPHTHALOCYANINES; ZINC(II); DERIVATIVES; Chemistry